Perry syndrome with progressive supranuclear palsy-like phenotype in a Portuguese family – Long-term clinical follow-up. (March 2021) - Barreto, Rui Duarte; Rodrigues, Rita; Roriz, José Mário; Alonso, Isabel; Magalhães, Marina
Highlights: Perry syndrome is caused by different DCTN1 gene mutations. Apathy, vertical gaze palsy, and falls may be initial symptoms, mimicking progressive supranuclear palsy. Weight loss and hypoventilation may be absent in early stages. Oculogyric crisis in Perry syndrome may respond to anticholinergics.